Analysis of a Novel Fluidic Oscillator under Several Dimensional Modifications - Kavoos Karimzadegan; Masoud Mirzaei; Josep M. Bergada (Applied Sciences, 2024)
To activate the boundary layer in Active Flow Control (AFC) applications, the use of pulsating flow has notable energy advantages over constant blowing/suction jet injections. For a given AFC application, five parameters, jet location and width, inclination angle, frequency of injection, and the momentum coefficient, need to be tuned. Presently, two main devices are capable of injecting pulsating flow with a momentum coefficient sufficient to delay the boundary layer separation: these are zero-net-mass-flow Actuators (ZNMFAs) and fluidic oscillators (FOs). In the present study, a novel FO configuration is analyzed for the first time at relatively high Reynolds numbers, and fluid is considered to be incompressible. After obtaining the typical linear correlation between the incoming Reynolds number and the outlet flow oscillating frequency, the effects of dimensional modifications on outlet width and mixing chamber wedge inclination angle are addressed. Modifications of the outlet width were observed to create large variations in FO performance. The origin of self-sustained oscillations is also analyzed in the present manuscript and greatly helps in clarifying the forces acting on the jet inside the mixing chamber. In fact, we can conclude by saying that the current FO configuration is pressure-driven, although the mass flow forces appear to be much more relevant than in previously studied FO configurations.